Pd nanocatalysts engineering for direct oxidation methane-to-methanol with 99.7% selectivity - Peilin Deng; Yueshan Xu; Daoxiong Wu; Ying Liang; Xue Zhang; Zhitong Wang; Jing Li; Xinlong Tian (Nature Communications)
Abstract Pd catalysts demonstrate remarkable activity and selectivity for the direct oxidation methane-to-methanol (DOMM) under mild conditions. However, understanding the structure–performance relationship is challenging because Pd catalysts used in existing studies have complex polycrystalline structures. In this work, well-defined Pd nanocrystals with controlled morphologies are synthesized and used as model systems to investigate the origins of the observed structure-activity differences. Our findings indicate that DOMM activity is primarily governed by crystal facet type rather than nanocrystal size. The lower d-band center of the Pd {111} facet weakens the adsorption strength of critical intermediates, including *O2 and *OH species, promoting H2O2 generation and CH3OH formation, respectively. Consequently, {111}-dominated octahedral Pd nanocrystals achieve an exceptional CH3OH yield of 201.8 mmol·gPd −1·h−1, three times higher than that of their {100}-dominated hexahedral counterparts. These results provide key insights into the structure-dependent behavior of Pd catalysts and pave the way for designing high-performance catalysts for DOMM.